238U–230Th–226Ra–210Pb–210Po Disequilibria Constraints on Magma Generation, Ascent, and Degassing during the Ongoing Eruption of Kīlauea. (16th August 2017) - Girard, Guillaume; Reagan, Mark K.; Sims, Kenneth W. W.; Thornber, Carl R.; Waters, Christopher L.; Phillips, Erin H.
Abstract: The timescales of magma genesis, ascent, storage and degassing at Kīlauea volcano, Hawai'i are addressed by measuring 238 U-series radionuclide abundances in lava and tephra erupted between 1982 and 2008. Most analyzed samples represent lavas erupted by steady effusion from Pu'u 'Ō'ō and Kūpahianaha from 1983 to 2008. Also included are samples erupted at the summit in April 1982 and March 2008, along the East Rift Zone at the onset of the ongoing eruption in January 1983, and during vent shifting episodes 54 and 56, at Nāpau crater in January 1997, and Kane Nui O Hamo in June 2007. In general, samples have small (∼4%) excesses of ( 230 Th) over ( 238 U) and ∼3 to ∼17% excesses of ( 226 Ra) over ( 230 Th), consistent with melting of a garnet peridotite source at melting rates between 1 × 10 –3 and 5 × 10 –3 kg m –3 a –1, and melting region porosity between ∼2 and ∼10%, in agreement with previous studies of the ongoing eruption and historical eruptions. A small subset of samples has near-equilibrium ( 230 Th/ 238 U) values, and thus were generated at higher melting rates. Based on U–Th–Ra disequilibria and Th isotopic data from this and earlier studies, melting processes and sources have been relatively stable over at least the past two centuries or more, including during the ongoing unusually long (>30 years) and voluminous (4 km 3 ) eruption. Lavas recently erupted from the East Rift Zone have average initial ( 210 Pb/ 226 Ra) values of 0·80 ± 0·11 (1σ), which we interpret to be the result of partitioning of 222 Rn into a persistently generated CO2 -rich gas phase over a minimum of 8 years. This ( 210 Pb) deficit implies an average magma ascent rate of ≤3·7 km a –1 from ∼30 km depth to the surface. Spatter and lava associated with vent-opening episodes erupt with variable ( 210 Pb) deficits ranging from 0·7 to near-equilibrium values in some samples. The samples with near-equilibrium ( 210 Pb/ 226 Ra) are typically more differentiated, suggesting decadal timescales of magma storage in shallow conduits or reservoirs that were not degassing. Lava and spatter samples erupted in the East Rift Zone and at the summit had ( 210 Po) ∼0 at the time of eruption, which results from efficient partitioning of Po into the CO2 - and SO2 -rich gas phases during and prior to eruption. Summit ash and Pele's hair samples from 2008 differ from lava and lapilli samples in that they have elevated initial ( 210 Po), ( 210 Pb/ 226 Ra), and Pb concentrations because of Po condensation on tephra particles, and incorporation of fumarolic Po and Pb into erupted tephra fragments during quenching.